Journeys of a constant thought. The development of Latin America as an object of knowledge (Andamios, Revista de Investigación Social, 2012)
In this article I propose a two moment characterization of the trajectory of Latin American critical thought. In the first, I recognize the shift form thought to theory, and the characteristic features that paradigms of self-reflection generate. The second moment is consecuence of the changes that military dictatorships involved for social reflection in the region. This new stage is characterized by the centrality of decolonial perspective. I reviewed the proposed pattern of modern-colonial domination in the light of new trends in critical thinking. Finally I note the importance of social movements as sources of knowledge.
Keywords: Latin american social thought; latin american social theory; paradigms; dependency; underdevelopment; decoloniality; epistemology